Bibliometric analysis of abrasion and erosion disaster mitigation: trends, key themes, and potential for global policy development - Sylvina Rusadi; Rahman Mulyawan; Utang Suwaryo; Neneng Yani Yuningsih (Cogent Social Sciences, 2024)
This research aims to identify and analyze publication documents on disaster mitigation due to abrasion and erosion and current global policy development through bibliometric analysis. Research data were obtained from the Scopus database and analyzed using Vooviewer software. Scopus was chosen because it is one of the most comprehensive and extensive global academic databases, enabling in-depth analysis of various scientific fields. The analysis results show that research interest in abrasion and erosion mitigation has increased over the past few years, with a significant increase in publications in certain periods. The main research themes identified include coastal erosion, land use change, machine learning, and policy aspects related to mitigation. The study findings also highlight the potential use of new technologies, such as machine learning, in erosion modeling and prediction. The findings provide a deeper understanding of the complexity of the abrasion and erosion problem and highlight the importance of a cross-disciplinary approach to addressing it. In addition, this study also identified some themes that require more attention, such as erosion rates, which may need to have received more attention in mitigation research. These findings can support governments and stakeholders in formulating effective policies and directing resources to mitigate abrasion and erosion.